THE EFFECT OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) LEARNING MODEL TO IMPROVE LEARNING OUTCOME OF INDONESIAN LANGUAGE IN DETERMINING SENTENCE OF ADVICE FOR GRADE 3 STUDENTS AT SD NEGERI 148 PEKANBARU - Ayu Nurzayyana; Indah Putri Danyati; Zeti Akmalia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research was conducted at SDN 148 Pekanbaru. The subjects of this study were 29 grade 3 students consisting of 17 male students and 12 female students. This research aims to improve the learning outcomes of Indonesian students by applying the Cooperative Integrated Reading and Composition (CIRC) learning model. The method used in this research was experiment. This research was conducted for 3 days, where the first day gave a pretest to students, the second day provided learning, and the third day was posttest. The results of the study were seen from the students' pretest and posttest. On the results of the pretest of 29 students, there were 13 students who completed and 16 other students who did not complete with an average of 68.03. Then in the posttest, the number of students who have completed has increased by 26 people while students who have not completed were 3 people so that an average of 80.62 was obtained which was relatively high. The results of t-test with tcount = 10.17 and ttable = 2.048, which can be concluded that tcount > ttable, then Ho is rejected and Ha is accepted, meaning that there were differences and increases in student learning outcomes at SD Negeri 148 Pekanbaru between before and after the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model.